MANAGEMENT OF PATIENTS WITH ACUTE KIDNEY INJURY - Belal, S. A. S.; Zolotarova, T. V.; Litvin, A. S. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Presented lecture is about management of a serious condition – acute kidney injury (AKI). It is intended for students, general practitioners, family physicians, therapists and those who may face with manifestations of AKI, and on which depends its timely diagnosis and the success of therapy. Definition, epidemiology, risk factors, causes, pathogenesis, classification, symptoms, diagnosis and differential diagnosis, treatment, complications, prognosis and prevention of AKI are described.Because of the morbidity and mortality associated with AKI, it is important to identify patients who are at high risk of developing this type of injury and to implement preventive strategies. Those at highest risk include adults older than 75 years; persons with diabetes or preexisting CKD; persons with medical problems such as cardiac failure, liver failure, or sepsis; and those who are exposed to contrast agents or who are undergoing cardiac surgery.